Prostitutes: vendors of another type - Muzvidziwa, Victor N. (2016)
Urban prostitution in Zimbabwe dates back over a century to the rise of colonial towns. In Zimbabwe employment opportunities in the settler towns attracted male migrants. Due to low wages and the provision of bachelor accommodation in towns, men generally left their families in the rural village.Most lived like single men, often divorced or rejected by their kin (van Onselen, 1976). For those women who migrated independently to town, the only viable occupation was prostitution. Despite the fact that prostitution was never legal during the colonial period and despite attempts to control it by using Vagrants Act, it thrived and still thrives. Prostitution remains largely as a 'hanging-on' strategy. This article explores prostitution in one of Zimbabwe' major towns - Masvingo - and demonstrates prostitutes' life situations, motivations and future plans. Their social and working lives, self-definition of their sex worker status, relationships with other prostitutes, the kinds of social networks they establish, their clients, incomes and expenditure patterns are some of the issues raised in this article. The impact of ESAP on prostitution, urban adjustments and coping mechanisms, are also discussed.